Knowledge organization and film production: interdisciplinary dialogues on film indexing under a socio-cultural perspective - Rosa Inês Novais Cordeiro; José Augusto Chaves Guimarães; Fernando Paes de Oliveira Chaves Guimarães (Informatio)
This study proposes to discuss the sociocultural approach in KO with focus on interdisciplinary relations, within the scope of film indexing in cinema collections, considering two perspectives: the process of film making and the documents generated during this journey; and the design of aspects utilized to analyze and represent films for an information service. For this, film production is considered as a long and complex process that goes through multiple stages, ultimately forming an extensive chain until the film is finalized. In this sense, even after completion, the filmic object still undergoes several phases in the exhibition stage. As a consequence, a proposal for the organic organization of a film's documentation, should consider its pre-production, production and post-production processes, in order to ensure, among other aspects, the context in which the records were created, as well as the discourses that permeate this process. Thus, the proposal for the organic organization of this knowledge must take into account the dynamic context in which it is produced, interpreted and used and some possible facets can be drawn up to lead to access points resulting from the film indexing process are proposed: Cast, Characters; Conflict Matrix; Film Story Summary; Space and Time; and Film Setting as well as the source documents that subsyde the analytic process.